Can a smartphone-delivered tool facilitate the assessment of surgical site infection and result in earlier treatment? Tracking wound infection with smartphone technology (TWIST): protocol for a randomised controlled trial in emergency surgery patients. Issue 10 (3rd October 2019) - McLean, Kenneth A; Mountain, Katie E; Shaw, Catherine A; Drake, Thomas M; Ots, Riinu; Knight, Stephen R; Fairfield, Cameron J; Sgrò, Alessandro; Skipworth, Richard J E; Wigmore, Stephen J; Potter, Mark A; Harrison, Ewen M
Abstract : Introduction: National data suggest that surgical site infection (SSI) complicates 2%–10% of general surgery cases, although the patient-reported incidence is much higher. SSIs cause significant patient morbidity and represent a significant burden on acute healthcare services, in a cohort predominantly suitable for outpatient management. Over three-quarters of UK adults now own smartphones, which could be harnessed to improve access to care. We aim to investigate if a smartphone-delivered wound assessment tool results in earlier treatment. Methods and analysis: This is a randomised controlled trial aiming to recruit 500 patients across National Health Service (NHS) hospitals. All emergency abdominal surgery patients over the age of 16 who own smartphones will be considered eligible, with the exclusion of those with significant visual impairment. Participants will be randomised in a 1:1 ratio between standard postoperative care and the intervention – use of the smartphone tool in addition to standard postoperative care. The main outcome measure will be time-to-diagnosis of SSI with secondary outcome measures considering use of emergency department and general practitioner services and patient experience. Follow-up will be conducted by clinicians blinded to group allocation. Analysis of time-to-diagnosis will be by comparison of means using an independent two sample t-test. Ethics and dissemination: This is the first randomised controlled trial on the use of a smartphone-delivered wound assessment tool to facilitate the assessment of SSI and the impact on time-to-diagnosis. The intervention is being used in addition to standard postoperative care. The study design and protocol were reviewed and approved by Southeast Scotland Research and Ethics Committee (REC Ref: 16/SS/0072 24/05/2016). Study findings will be presented at academic conferences, published in peer-reviewed journals and are expected in 2020. A written lay summary will be available to study participants on request. Trial registration number: NCT02704897 ; Pre-results.